The effects of a Job Training Partnership Act program on "at-risk" youths? level of self esteem, locus of control, and endorsement of irrational beliefs - Koehler, Gretchen (My University, 1986)
Fourteen youth from the ages of 16 to 21 years old were enrolled in a JTPA troubled youth program, administered by Western Wisconsin Coulee Region Community Action Program in La Crosse, WI, were assessed on the Janis Field Feelings of Inadequacy Scale, the Self Esteem Scale, an Abbreviated 11-item Rotter I-E Scale, and the Irrational Beliefs Test, completing the treatment. The work experience included an 8 hour job seeking skills workshop which emphasized resume' preparation, interviewing skills, and job search strategies.
Keywords: Social work with youth; Occupational training -- Psychological aspects